Metal Music as a Medium of Da'wah Communication (Album 7:172 Band Purgatory) - Dhista Almayda*, Sabian Ray; Zulfiningrum, Rahmawati (Universitas Syiah Kuala, 2023)
Purgatory is a metal band from Jakarta that creates Music that contains a Message of da'wah in it. Purgatory released an album entitled